Optimalisasi Waktu Pelaksanaan Proyek Rekonstruksi Jalan Batanghari II-Zona Lima-Muara Sabak dengan Metode CPM (Critical Path Metode) - Winda Dwiarti; Elvira Handayani; Kiki Rizky Amalia (Universitas Batanghari Jambi, 2022)
Project Management is planning, compiling, and controlling the schedule of project activities. Good time control can help implement projects that have been in accordance with the planned time. This project uses the Critical Path Method. CPM is a technique of analyzing the network of activities/activities when executing a project in order to predict the total duration. The purpose of this study is to analyze the new CPM Network after optimizing the work time so that there will be no delays in the Reconstruction work of Batanghari II Road – Zone Lima – MA.Sabak. Initially, the scheduling of the Batanghari II-Zona Lima-Muara Sabak Road Reconstruction Project took 34 calendar days. The author speeds up the time on the following 4 jobs: 1. Mobilization (AA) from 2 days to 1 day. 2. Management and work safety from 2 days to 1 day. 3. Environmental protection from 2 days to 1 day. 4. Selected stockpile from excavated sources from 7 days to 5 days. So the work time becomes 33 calendar days.